MEMBEDAH PEMANFAATAN TEKNOLOGI MULTIMEDIA YOUTUBE SEBAGAI ALAT PROMOSI PERPUSTAKAAN: STUDI KASUS CHANNEL YOUTUBE PERPUSTAKAAN UIN RADEN FATAH PALEMBANG - Dzakirah Tsabitah; Misroni; Sahro Ramadona (2025)
The utilization of multimedia technology, particularly the YouTube platform, has emerged as a new strategy for promoting library services and collections in the digital era. This study aims to analyze the effectiveness and patterns of usage of the YouTube channel of the UIN Raden Fatah Palembang Library as a promotional medium, using a descriptive comparison with the YouTube channel of the University of Indonesia Library. The research method employed is literature review and content analysis with a qualitative approach. The findings reveal that the UIN Raden Fatah Library’s YouTube channel focuses more on documenting events and promoting circulation services, whereas the University of Indonesia Library features more interactive videos such as tutorials, webinars, and regular digital educational content. These differing content strategies influence the level of engagement and audience reach. This study recommends optimizing the use of multimedia technology through more strategic content planning that aligns with user needs.